DEVELOPMENT OF CONTROLLED ACOUSTIC DUST GENERATOR - Insan Kamil, Aji
Air pollution has become a problem in several cities around the world because of its effect on environment and human's health. One of the pollutant which hazard human’s health is particulate matter (PM). In order to study this matter, we need an instrument to generate PM named aerosol generator or dust generator for coarse particle. In this study, a dust generator and its generated particle instrumentation system were designed and assembled. The developed dust generator use acoustic signal from a loudspeaker which received input signal from a signal generator to generate particle into the air before the particle is being moved through air pipe. Generated particle measurement uses SHARP GP2Y1010AU0F (GP2Y) and ATMega328P microcontroller to read and process the data of particle that pass through detection area of sensor. In this work, we also calibrate GP2Y sensor using Optical Particle Counter (OPC) as reference instrument. The convertion of particle number concentration to mass concentration is done using certain approximation and an assumption that particle’s shape is spherical. Open loop control on fugitive parameter is done in order to get desirable value. Afterwards, we do parameter tuning on physical parameters which affect the output of dust generator. Furthermore, this tuning process’ aim is to observe the effect of airflow, input signal amplitude, input signal frequency, and input waveform signal against particle concentration. The results show that mentioned parameters have effect on particle concentration. Signal amplitude has a linear relation against particle concentration while both airflow’s and frequency’s relations against particle concentration is not linear. Meanwhile, particle concentrations generated by noise signal input are much smaller than those generated by single frequencies and also time-dependent. Forth, an empirical model which express mass concentration as function of input voltage and frequency is proposed in this research. Finally, coefficient of variation (KV) of particle concentration generated from acoustic dust generator is varied between 0.38% - 5.51%, these values is acceptable according to EPA standard and other dust generators which have KV varied between 6% - 24%.